2016
DOI: 10.3109/13651501.2016.1141960
|View full text |Cite
|
Sign up to set email alerts
|

Insight and recovery in schizophrenic patients

Abstract: Only a small proportion of schizophrenic patients achieved recovery, therefore greater patient's insight could have prognostic validity in terms of treatment outcome. More sensitive instruments and a larger sample are necessary to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
13
0
3
Order By: Relevance
“…Cannavo et al 72 documented that improvement in psychosocial function was associated with significant improvements in clinical insight, while Klaas et al 73 found that good clinical insight had a positive effect upon social function, but that changes in social function did not influence insight in first-episode psychosis.…”
Section: Insight and Outcomementioning
confidence: 99%
“…Cannavo et al 72 documented that improvement in psychosocial function was associated with significant improvements in clinical insight, while Klaas et al 73 found that good clinical insight had a positive effect upon social function, but that changes in social function did not influence insight in first-episode psychosis.…”
Section: Insight and Outcomementioning
confidence: 99%
“…Only 12% of respondents met all the criteria for remission for 2 years or longer.In the study group, an improvement in the level of insight was also found, especially in patients treated with second generation antipsychotics (SGA). The recovery of insight was positively correlated with female sex, older age, SGA treatment, predisease social adaptation and low level of negative symptoms of schizophrenia at the beginning of the study [23].…”
Section: Recovery and Stigmamentioning
confidence: 91%
“…"Insight and recovery in schizophrenic patients" było zbadanie korelacji między wglądem i zdrowieniem u pacjentów ze schizofrenią według kryteriów zarówno objawowej jak i funkcjonalnej remisji. Odzyskiwanie wglądu było pozytywnie skorelowane z płcią żeńską, starszym wiekiem, leczeniem, wstępnie chorobową adaptacją społeczną i niskim poziomem negatywnych objawów schizofrenii na początku badania [23].…”
unclassified
“…Yildiz's study found that at the end of 5 years, only 35.7% of patients achieved recovery criteria. When the international literature is examined, Lambert et al reported that only 26.6%, Haro et al reported that 25.4%, and Cannavò et al reported that 12% of patients with schizophrenia showed functional recovery at the end of 2 years. In addition, Boyer et al found that only 30% to 38% of patients with recovery showed really satisfactory functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Study results showing low levels of functional recovery and QOL in patients with schizophrenia emphasize the importance of this issue . Patients with low levels of functioning are a significant burden to family, caregivers and to society, and the disease leads to high costs.…”
Section: Introductionmentioning
confidence: 99%